Non-alcoholic Fatty Liver Disease Is Associated With Cardiovascular Outcomes in Subjects With Prediabetes and Diabetes: A Prospective Community-Based Cohort Study - Song, Qi-Rui; Liu, Shuo-Lin; Bi, Ya-Guang; Chen, Shuo-Hua; Wu, Shou-Ling; Cai, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: There have been no studies of the combined effect of non-alcoholic fatty liver disease (NAFLD) and prediabetes on cardiovascular events (CVEs). We performed a community-based cohort study to evaluate the relationship between NAFLD and CVEs in patients with prediabetes or diabetes. Methods: We enrolled 71,852 participants from the Kailuan study who had not experienced CVEs, after excluding alcohol abuse and other liver diseases. NAFLD was assessed using abdominal ultrasonography. Besides, participants were categorized by glucose metabolism status [normal glucose regulation (NGR), pre-diabetes (pre-DM), and diabetes mellitus (DM)]. All subjects were followed up for the occurrence of CVEs. Results: During a median of 13.01 (0.64) years of follow-up, 6,037 CVEs occurred. NAFLD was present in 22,525 (31.3%), and compared with participants without NAFLD, those with NAFLD had a 12.3% (95% confidence interval (CI) 1.059–1.191, P<0.001) higher risk of CVEs, after adjustment for potential confounders. The hazard ratios for patients with mild, moderate, and severe NAFLD were 1.104 (95% CI 1.035–1.179, P<0.001), 1.149 (95% CI 1.055–1.251, P<0.001), and 1.235 (95% CI 1.059–1.441, P<0.001), respectively. Moreover, participants with pre-DM plus NAFLD and participants with DM plus NAFLD had 1.267-fold (95% CI 1.151–1.395, P<0.001) and 1.829-fold (95% CI 1.666–2.008, P<0.001) higher risks of CVEs, respectively, compared with those with NGR and no NAFLD. The addition of the combination of NAFLD and glucose metabolism status to the crude Cox model increased the C-statistic by 0.0066 (0.0053–0.0080, P<0.001). Conclusions: NAFLD is associated with higher risks of CVEs. Moreover, NAFLD is an independent predictor of CVEs in patients with pre-DM, suggesting that NAFLD may provide greater risk predictive value for patients with prediabetes.